Dicer regulates Xist promoter methylation in ES cells indirectly through transcriptional control of Dnmt3a. - Nesterova, T; Popova, B; Cobb, B; Norton, S; Senner, C; Tang, Y; Spruce, T; Rodriguez, T; Sado, T; Merkenschlager, M; Brockdorff, N (2008)
BACKGROUND: X chromosome inactivation is the mechanism used in mammals to achieve dosage compensation of X-linked genes in XX females relative to XY males. Chromosome silencing is triggered in cis by expression of the non-coding RNA Xist. As such, correct regulation of the Xist gene promoter is required to establish appropriate X chromosome activity both in males and females. Studies to date have demonstrated co-transcription of an antisense RNA Tsix and low-level sense transcription prior to onset of X inactivation. The balance of sense and antisense RNA is important in determining the probability that a given Xist allele will be expressed, termed the X inactivation choice, when X inactivation commences. RESULTS: Here we investigate further the mechanism of Xist promoter regulation. We demonstrate that both sense and antisense transcription modulate Xist promoter DNA methylation in undifferentiated embryonic stem (ES) cells, suggesting a possible mechanistic basis for influencing X chromosome choice. Given the involvement of sense and antisense RNAs in promoter methylation, we investigate a possible role for the RNA interference (RNAi) pathway. We show that the Xist promoter is hypomethylated in ES cells deficient for the essential RNAi enzyme Dicer, but that this effect is probably a secondary consequence of reduced levels of de novo DNA methyltransferases in these cells. Consistent with this we find that Dicer-deficient XY and XX embryos show appropriate Xist expression patterns, indicating that Xist gene regulation has not been perturbed. CONCLUSION: We conclude that Xist promoter methylation prior to the onset of random X chromosome inactivation is influenced by relative levels of sense and antisense transcription but that this probably occurs independent of the RNAi pathway. We discuss the implications for this data in terms of understanding Xist gene regulation and X chromosome choice in random X chromosome inactivation.